A Deep‐Cycle Aqueous Zinc‐Ion Battery Containing an Oxygen‐Deficient Vanadium Oxide Cathode. Issue 6 (27th December 2019) - Liao, Meng; Wang, Jiawei; Ye, Lei; Sun, Hao; Wen, Yunzhou; Wang, Chuang; Sun, Xuemei; Wang, Bingjie; Peng, Huisheng
Abstract: Rechargeable aqueous zinc‐ion batteries are attractive because of their inherent safety, low cost, and high energy density. However, viable cathode materials (such as vanadium oxides) suffer from strong Coulombic ion–lattice interactions with divalent Zn 2+, thereby limiting stability when cycled at a high charge/discharge depth with high capacity. A synthetic strategy is reported for an oxygen‐deficient vanadium oxide cathode in which facilitated Zn 2+ reaction kinetic enhance capacity and Zn 2+ pathways for high reversibility. The benefits for the robust cathode are evident in its performance metrics; the aqueous Zn battery shows an unprecedented stability over 200 cycles with a high specific capacity of approximately 400 mAh g −1, achieving 95 % utilization of its theoretical capacity, and a long cycle life up to 2 000 cycles at a high cathode utilization efficiency of 67 %. This work opens up a new avenue for synthesis of novel cathode materials with an oxygen‐deficient structure for use in advanced batteries. Abstract : A high‐performance cathode for use in deep‐cycle aqueous zinc‐ion batteries was created by extracting oxygen from vanadium oxide lattices. The mobility of Zn 2+ is facilitated and capacity and reversibility of the battery thereby improved. The cathode achieves a stability of 200 cycles with a high capacity of 400 mAh g −1 and a utilization efficiency of 95 %, and a long‐term stability of 2 000 cycles at a utilization of 67 %. Key: graphene oxide (GO).